NIRS as a tool for assaying emotional function in the prefrontal cortex - Doi, Hirokazu; Nishitani, Shota; Shinohara, Kazuyuki (Frontiers in Human Neuroscience, 2013)
Despite having relatively poor spatial and temporal resolution, near-infrared spectroscopy (NIRS) has several methodological advantages compared with other non-invasive measurements of neural activation. For instance, the unique characteristics of NIRS give it potential as a tool for investigating the role of the prefrontal cortex (PFC) in emotion processing. However, there are several obstacles in the application of NIRS to emotion research. In this mini-review, we discuss the findings of studies that used NIRS to assess the effects of PFC activation on emotion. Specifically, we address the methodological challenges of NIRS measurement with respect to the field of emotion research, and consider potential strategies for mitigating these problems. In addition, we show that two fields of research, investigating (i) biological predisposition influencing PFC responses to emotional stimuli and (ii) neural mechanisms underlying the bi-directional interaction between emotion and action, have much to gain from the use of NIRS. With the present article, we aim to lay the foundation for the application of NIRS to the above-mentioned fields of emotion research.